A monograph of the magazine <Litoral>: The Madness. Art & Literature - Francisco Herrera-Rodríguez (Universidad de Alicante, 2018)
In these pages we present a review of the number 263 of the magazine <Litoral>, a publication founded in Malaga in 1926 by Emilio Prados and Manuel Altolaguirre, who gave voice to the so-called 'Generation of 27'. This issue, published in 2017, is dedicated to madness in art and literature.